Kepribadian Hardiness dengan Strategy Coping Anggota Polisi - Naura Alfidha; Desy Arisandy (Ilmu Psikologi Universitas Yudharta Pasuruan, 2023)
The police as individuals cannot be separated from various obstacles and problems that are often faced. There are so many tasks and authorities that they carry, in their daily implementation in the field sometimes many problems arise in the work, such as not meeting operational targets, pressure from superiors, psychological and physical fatigue, erratic working hours and other problems. To meet the demands of a task like this requires a healthy mental condition for the police, one of which is being able to face and overcome problems and pressures that arise so as to avoid stressful conditions. In this study, the aim of this study was to determine the relationship between personality hardiness and coping strategies. The method used by the researcher is quantitative with purposive random sampling technique. The population in this study amounted to 150 police officers with a sample of 105 police officers. Prior to this research, a trial was conducted on 45 police officers. The results of this study indicate that there is a positive relationship between the personality of hardiness and the coping strategy of members of the Sarolangun Police Police. These results can be seen from the value of the correlation coefficient r = 0.339 or 33.9% with a significance value (P) = 0.000 < 0.01. This shows that there is a very significant relationship between the personality of hardiness and the coping strategy members of the Polres Sarolangun.